Health Education and Its Effect on Adolescent Knowledge and Attitudes in the Prevention of Sexually Transmitted Diseases - Natalia Debi Subani; Yulianti Kristiani Banhae; Roswita V.W.R. Roku; Oklan BT Liunokas (Indonesian Journal of Global Health Research, 2022)
Sexually transmitted infections are one of the main health problems of adolescents. Every teenager is at high risk for developing sexually transmitted infections (STIs) for various reasons such as frequency of unprotected sexual intercourse, being more biologically susceptible to infection, involving relationships of limited duration, and possible difficulties accessing the health care system. The impact when a teenager is exposed to STDs is that it can cause acute symptoms, chronic infections such as infertility, ectopic pregnancy, cervical cancer and sudden death in infants and adults. adolescents to increase the knowledge, attitudes and practices of adolescents in behaviour. Analyze the effect of health education on the knowledge and attitudes of adolescents in preventing the transmission of sexually transmitted diseases. The type of research used is quasi-experimental with a pre-test and post-test with a control group design. There is an effect of health education on the knowledge and attitudes of adolescents in preventing the transmission of sexually transmitted diseases. Health education plays a very important role in increasing knowledge and changing attitudes of adolescents in preventing the transmission of sexually transmitted diseases.